PENDETEKSI KADAR ALKOHOL DALAM TUBUH MANUSIA MELALUI HEMBUSAN NAFAS UNTUK PENGEMUDI MOBIL - Langgeng Wijaya; Edy Kurniawan; Didik Riyanto (KOMPUTEK, 2019)
Alcohol is a drink containing ethanol in it and people who are ordinary alcohol or drinks that can be intoxicating, the impact of consuming this alcohol a lot and one of them is a diversion campaign produced by the driver. From some of these questions, the idea emerged for the detection of "Detection of Alcohol Content in the Body Through Talking Breath for Car Drivers" the design of this tool is expected to be able to be earlier or be able to prevent accidents caused by motorists consuming alcohol while driving. This design is made by finding references derived from journals, books and articles, which then make a plan or drawing that is intended for design such as what will be made, design in the form of hardware that connects the input devices, processes and outputs, while the software consists of programs as system drivers. After the design is complete, the tool will be designed and analyzed. Based on the analysis carried out, the system can protect alcohol with the help of the tgs2620 sensor if the sensor detects more than 100ppm of gas it will be processed by the atmega32 microcontroller and the output released consists of an LCD which is useful as a power and ppm viewer produced by the sensor, leds and buzzer as indicator, dc motor is useful as a prototype of a car that can be run or not and isd 1820 (voice recording) consumes alcohol for the car driver.